MBL2 gene polymorphism rs1800450 and rheumatic fever with and without rheumatic heart disease: an Egyptian pilot study - Maher Hassan Gomaa; Shawkey Sadik Ali; Aya Mohamed Fattouh; Hala Salah Hamza; Mohamed Mohamed Badr (BMC, 2018)
Abstract Background Rheumatic fever (RF) is the result of an autoimmune response to pharyngitis caused by infection with Streptococcus pyogenes. RF is most prevalent in Africa and the Middle East. Rheumatic heart disease (RHD) is the most serious complication of RF. Mannose-binding lectin 2 gene (MBL2) has been reported to be correlated with different cardiac conditions. In Egyptian patients as a new studied ethnic population, it is the first time to evaluate the association between MBL2 gene polymorphism rs1800450 and RF with and without RHD. Methods One hundred and sixty RF patients (80 with RHD and 80 without RHD) and eighty healthy ethnically matched controls were studied. MBL2 (rs1800450) was genotyped by real-time PCR using TaqMan® allele discrimination assay. The MBL level was measured by ELISA. Westergren erythrocytes sedimentation rate (ESR), anti-streptolysin O titer (ASOT), C-reactive protein (CRP) and complements (C3 and C4) were determined. Results The AA genotype with high production of MBL was associated with increased risk of RHD more than the B allele carrying subjects. However, MBL2 genotype related to the low production of MBL was more frequently observed in those patients without RHD. Conclusions Our results suggested the involvement of MBL2 (rs1800450) polymorphism and its protein in RHD pathogenesis. Also, it might be a promising future strategy to utilize this polymorphism to help differentiate patients with RHD from those without RHD.